Incidence of sudden cardiac death after heart transplantation. (25th November 2020) - Bonnet, G; Coutance, G; Waldmann, V; Aubert, O; Asselin, A; Raynaud, M; Racape, M; Bories, M.C; Varnous, S; Rouvier, P; Bruneval, P; Leprince, P; et al.
Abstract: Background: Sudden cardiac death (SCD) is a major contributor to the rate of mortality after heart transplantation. However, little is known about the incidence of SCD in heart recipients. Objective: To assess the incidence of SCD after heart transplantation. Methods: We enrolled consecutive patients transplanted between 2004 and 2017 in two French referral centers. We defined 7 main groups of causes of deaths: SCD, cardiovascular (including Cardiac allograft vasculopathy), infection, primary graft dysfunction, graft failure (including late graft dysfunction, rejection), malignancy and others. Causes of deaths were independently adjudicated by two senior cardiologists based on the analysis of death certificates and medical records. Discrepancies were resolved by discussion until a consensus was made. SCD was defined as an unexpected out-of-hospital cardiac arrest without obvious non-cardiac cause, in the first hour after initiation of symptoms. Results: A total of 1, 363 patients were included. The median follow-up post-transplant was 3.99 years (IQR=0.49–7.49). 450 patients (33%) deceased during the first year. The leading cumulative causes of death in the first year after transplantation were infection, primary graft failure, multiple organ failure during the period in intensiv car unit. Beyond the post-operativ high-risk period of the first year, the leading cumulative cause of death was SCD: among the 213 deaths that occurred beyond the first year, 44 patients (21%) died from SCD. In this period, the incidence rate of SCD reached 0, 82 per 100 person-year (95% CI: 0.51–2.05). Conclusion: In a large multicentric and highly phenotyped cohort of heart transplant recipients, the leading cumulative cause of death beyond the first-year post transplant was sudden cardiac death. Our results open discussion on management of heart recipient, such as the implementation of cardioverter-defibrillators. Funding Acknowledgement: Type of funding source: None